OPTIMIZATION TO MINIMIZING DISTANCE CARS OF FIRE EXPORTER IN INDUSTRIAL REGION SIER SURABAYA: OPTIMIZATION TO MINIMIZING DISTANCE CARS OF FIRE EXPORTER IN INDUSTRIAL REGION SIER SURABAYA - Muhamad Abdul Jumali (UNIPA PRESS, 2018)
Various fire infrastructure in Surabaya has been built, but the number of fire incident is less suitable with the standard of disaster response time. This study was conducted to determine the distribution of minimization of fire engine mileage in SIER Industrial Area of ​​Surabaya. The analytical method used is qualitative descriptive by comparing existing condition, criteria, and policy review that exist in SIER Industrial Area of ​​Surabaya with data of fire service post service in Surabaya City to know unreached area of ​​fire post service and have high risk potential Will be a fire disaster in the SIER Industrial Area of ​​Surabaya. Next determine the factors and criteria for determining the location of firefighting post based on existing policy studies and conditions. Factors determining the location of firefighting in Surabaya City is a function of the building based on the type of land use, the density of the net population, the density of the building, the range of fire service, the radius of the water supply range, the incidence of fire, the time of fire disaster response, the availability of land, and the class of road. The result of this research is the implementation of building protection management on building function in industrial area, procurement of socialization and education of fire prevention for the community, coordinating with traffic police to facilitate path of location achievement